INTERVENÇÃO NUTRICIONAL EM CIRURGIA BARIÁTRICA: UM RELATO DE CASO - Farias, Myrla C. de Oliveira; Dias, Celina de Azevedo; Amaral, Ariana de A. G. Ferreira do (Gep News, 2017)
Tipo de Apresentação: Comunicação Oral